Growth inhibitory and adjuvant therapeutic potential of aqueous extract of Triticum aestivum on MCF-7 and HeLa cells - Hussain, A.; Gheewala, T.M.; Vas, A.J.; Shah, K.; Goala, P.; Khan, S.; Hinduja, S.; Sharma, C. (Experimental Oncology, 2014)
Aim: The purpose of the present study is to evaluate the potent growth inhibitory effects of aqueous wheatgrass extract (AWE) alone and in combination with cisplatin on human breast and cervical cancer cells. Materials and Methods: The cytotoxic potential of AWE alone and in combination with cisplatin was evaluated on human breast and cervical cancer cells (MCF-7 and HeLa) by cell viability assay. Further, the mode of cell death induced by AWE was determined by nuclear morphological examination and cell cycle analysis. These effects were then correlated with the expression of genes involved in apoptosis and proliferation (cyclin D1 and Bax) by RT-PCR. Results: AWE showed dose- and time dependent selective cytotoxicity towards the cancerhighlighting its safe profile. Lower dose combinations of AWE and cisplatin induced increased growth inhibition compared with the individual drugs on both cell lines (combination index < 1) indicating strong synergistic interactions. AWE was found to induce apoptosis and arrested the cells at G0–G1 phase of the cell cycle which correlated with the modulation of expression of bax and cyclin D1 in a time-dependent manner in MCF-7 and HeLa cells. Conclusion: These results suggest that the anti-cancer potential of AWE may be due to apoptosis induction and its anti-proliferative properties. This study also provides the first evidence demonstrating synergism between AWE and cisplatin, which may enhance the therapeutic index of prevention and/or treatment of human breast and cervical cancer. Key Words: Bax, cisplatin, combination, cyclin D1, synergistic, wheatgrass.